Dimensions of responsibility in medical genetics: exploring the complexity of the "duty to recontact". Issue 3 (3rd July 2018) - Doheny, Shane; Clarke, Angus; Carrieri, Daniele; Dheensa, Sandi; Hawkins, Naomi; Lucassen, Anneke; Turnpenny, Peter; Kelly, Susan
Abstract : Discussion of a "duty to recontact" emerged as technological advances left professionals considering getting back in touch with patients they had seen in the past. While there has been much discussion of the duty to recontact as a matter of theory and ethics, there has been rather little empirically based analysis of what this "duty" consists of. Drawing on interviews with 34 professionals working in, or closely with, genetics services, this paper explores what the "duty to recontact" means for healthcare professionals involved in genetics. Using a discourse analytic framework, the paper identifies three system generated discourses on recontact (governance, legal and responsibilizing discourses) and three lifeworld discourses (situating recontact as a formal duty; more loosely as an obligation; and as a personal sense of responsibility). In summary, the paper shows that the "duty" to recontact involves a complex interplay of system responsibilities with professional duties, responsibilities and obligations.